Effect of home-used water purifier on fluoride concentration of drinking water in southern Iran - Zohreh Jaafari-Ashkavandi; Mehdi Kheirmand (Wolters Kluwer Medknow Publications, 2013)
Background: Fluoride in drinking water plays a key role in dental health. Due to the increasing use of water-purifier, the effect of these devices on fluoride concentration of drinking water was evaluated. Materials and Methods: Drinking water samples were collected before and after passing through a home water-purifier, from four different water sources. The fluoride, calcium and magnesium concentration of the samples were measured using the quantitative spectrophotometery technique. Data were analyzed by the Wilcoxon test. P value < 0.1 was considered as significant. Results: The result showed that the concentration of fluoride was 0.05-0.61 ppm before purification and was removed completely afterward. Furthermore, other ions reduced significantly after treatment by the water purifier. Conclusion: This study revealed that this device decreases the fluoride content of water, an issue which should be considered in low and high-fluoridated water sources.